Productive Performance of Ouled Djellal Ewesin Arid and Semi-arid Zones of Eastern Algeria: Productive performance of Ouled Djellal ewes - Douh, Mourad; N Rebai; Y. Gouasmia; S. Rebai; C. Aissaoui (Annals of Arid Zone, 2024)
Reproduction contributes directly to farm profitability, and is summarized in economic indicators and performance analysis. The study was carried out on nine farms with a total of 762 breeding ewes of the Ouled Djellal breed (91 sedentary, 323 semi-sedentary and 348 transhumant). 165 ewes aged one year, 211 ewes aged two years, 290 ewes aged three years and 96 ewes aged between three to four years were used. With 578 ewes confirmed pregnant, 681 lamb births were recorded: 265 in the first group (winter), 280 in the second group (summer), 105 in the third group (summer), and 32 in the fourth group (autumn back-season), with 118 declared mortality losses, of which 36 lambs were stillborn. Twelve-month zootechnical data, such as age at first lambing, lambing interval, fertility rate, prolificacy or litter size, fertility rate and mortality losses were recorded from the raw database collected. Results showed that the average age at first lambing was 359.50±21.13 days. The interval between two parturitions showed a reduction in time in relation to lambing rank (cyclic number of lambings) and ewe age. Average litter size was 1.06±0.04 lambs for sedentary ewes, 1.17±0.03 lambs for semi-transhumant ewes and 1.21±0.05 lambs for transhumant ewes. Fertility and fecundity were 65% and 147.06% respectively. A mortality rate of 16.33% was recorded. Despite these differences between seasons, the origins of which are discussed, the reproductive performances analyzed were encouraging overall for improving the breed’s profitability. With the exception of seasonal mortality, which showed a non-significant difference between autumn and spring, the results for the other performance parameters showed a highly significant difference.